Application Of Maqasid Al-syariah To Preserve Religion And Intellectual On The Prohibition Of Spreading And Practicing False Hadis In Malaysia - Nur Afifi Bin Alit; Shumsudin Yabi; Mohd Yusuf Ismail (HRMARS (www.hrmars.com), 2024)
Indexed by ERA